2016
DOI: 10.1371/journal.pone.0150287
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Type I Collagen by Fibroblast Activation Protein-α Enhances Class A Scavenger Receptor Mediated Macrophage Adhesion

Abstract: Pathophysiological conditions such as fibrosis, inflammation, and tumor progression are associated with modification of the extracellular matrix (ECM). These modifications create ligands that differentially interact with cells to promote responses that drive pathological processes. Within the tumor stroma, fibroblasts are activated and increase the expression of type I collagen. In addition, activated fibroblasts specifically express fibroblast activation protein-α (FAP), a post-prolyl peptidase. Although FAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 62 publications
1
47
0
Order By: Relevance
“…This result is similar to FAP activity on fibrillar collagens, which is dependent on initial cleavage by MMP collagenases( 85 , 86 ). FAP cleavage of collagen I was shown to enhance macrophage adhesion in vitro , an effect which is independent of integrin binding but at least partially mediated by the macrophage scavenger receptor SR-A( 87 ). Given that some tumor-associated macrophages express FAP, it is intriguing to speculate that FAP expression by macrophages might promote their recruitment to and/or retention by the TME.…”
Section: Molecular Biology Of Fapmentioning
confidence: 99%
“…This result is similar to FAP activity on fibrillar collagens, which is dependent on initial cleavage by MMP collagenases( 85 , 86 ). FAP cleavage of collagen I was shown to enhance macrophage adhesion in vitro , an effect which is independent of integrin binding but at least partially mediated by the macrophage scavenger receptor SR-A( 87 ). Given that some tumor-associated macrophages express FAP, it is intriguing to speculate that FAP expression by macrophages might promote their recruitment to and/or retention by the TME.…”
Section: Molecular Biology Of Fapmentioning
confidence: 99%
“…High numbers of cancer-associated fibroblasts are often observed in tumors, suggesting that cellular contractions from cancer-associated fibroblasts may dramatically deform the ECM to potentially aid the recruitment of α2β1-expressing TAMs locally. Moreover, scavenger receptor A (SR-A) and CD36 mediate macrophage adhesion to modified or denatured forms of type I and IV collagen, which are often found in inflammatory conditions (92)(93)(94). CD36 is upregulated in alternatively activated macrophages (95), and SR-A is upregulated by macrophages when co-cultured with cancer cells (96).…”
Section: Effects Of Integrin Activation On Macrophagesmentioning
confidence: 99%
“…CD36 is upregulated in alternatively activated macrophages (95), and SR-A is upregulated by macrophages when co-cultured with cancer cells (96). Interestingly, SR-A expressing TAMs colocalize in the stroma of tumors with FAP+ cancer associated fibroblasts that cleave collagen fibers to enhance TAM retention via SR-A mediated adhesion (94). SR-A-mediated macrophage adhesion plays an important role in cancer, as demonstrated by the prevention of ovarian cancer progression in mice treated with SR-A inhibitors (96,97).…”
Section: Effects Of Integrin Activation On Macrophagesmentioning
confidence: 99%
“…45,46 Mazur et al reported that type I collagen cleaved by FAP from activated fibroblasts, a post-prolyl peptidase, could act as the substrate of macrophages which recognized by macrophages class A scavenger receptors (SR-A); therefore, it increased the macrophages adhesion in cancer. 47 Tumour-associated macrophages (TAMs) consist of two groups with different phenotypes. M1 macrophages play an anti-tumour role by activating the immune system and producing reactive oxygen species, nitric oxide and TNF.…”
Section: Interaction Between Cancer-associated Fibroblasts and Macrmentioning
confidence: 99%